MERCHANDISE INVENTORY PADA ACCURATE SOFTWARE TRAINING DI SMA KRISTOFORUS 1 JAKARTA - Sastra, Emillia; Gunawan, Felicia; Amelia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Community Service (PKM) is a form of the Tri Dharma of Higher Education by channeling knowledge to the community. The partner is SMA Kristoforus 1 Jakarta which is located on Jalan Rahayu No. 1A, West Jakarta. A meeting with the school to discuss the problems faced is the beginning of the implementation of this PKM. After discussion, it was seen that SMA Kristoforus 1 Jakarta welcomed this training so that the proposal was submitted to LPPM Tarumanagara University. This training activity includes providing modules, practice questions, quizzes, and questionnaires. By holding this training, students at SMA Kristoforus 1 Jakarta can get to know the accounting software, namely Accurate. It is hoped that this activity can increase the knowledge of SMA Kristoforus 1 Jakarta students in the field of accounting. This training also acts as a complement to the accounting theory lessons that students at Kristoforus 1 Jakarta High School have received. Not only that, but this activity is also expected to illustrate accounting practices in the workplace. PKM activities are also beneficial for the Faculty of Economics, Tarumanagara University by fostering good relations with SMA Kristoforus 1 Jakarta and are a way of sharing knowledge and experience. From the results of direct observations made during the training, it can be concluded that the students of SMA Kristoforus 1 Jakarta showed an interest in Accurate. The training material provided has also been well received and understood by the students of SMA Kristoforus 1 Jakarta.